Pengaruh Profitabilitas, Opini Audit, Ukuran Perusahaan Dan Pergantian Auditor Terhadap Audit Delay Dengan Audit Tenure Sebagai Variabel Moderating Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Annisa Nauli Sinaga; Iskandar Iskandar; Suriadi Suriadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
Companies that enter the Indonesian capital market must publish financial statements that have been audited by an independent auditor no later than 90 days after the end of the annual financial reporting period, which is March 31. This study aims to determine the effect of profitability, audit opinion, company size and auditor turnover on audit delay with audit tenure as a moderating variable in Manufacturing Companies listed on the Indonesia Stock Exchange. This study uses associative. The population in this study were 177 financial statements of manufacturing companies. The research sample is 31 financial statements. The result is that profitability, audit opinion and auditor turnover have no effect on audit delay of consumer goods companies listed on the Indonesia Stock Exchange. Company size has an effect on audit delay in Consumer Goods Companies listed on the Indonesia Stock Exchange that profitability, audit opinion, company size, and auditor turnover simultaneously have a positive and significant effect on audit delay. Audit tenure is not a moderating variable that can strengthen or weaken the relationship between profitability, company size, audit opinion, auditor turnover and audit delay in manufacturing companies listed on the Indonesia Stock Exchange. Keyword: Profitability, Audit Opinion, Company Size, Auditor Switching Audit Delay and Audit Tenure